Taking the University to the Classroom Teacher: Field-Based Graduate Programs - Gerald Douglass Bailey (Educational Considerations, 1975)
This field-based master's program is an innovative approach to graduate study in education. The program has received positive responses from all involved. One reason is that the faculty were careful not to wrap an old program in new paper and fancy ribbon.